Bilateral pleural effusion and pneumomediastinum: rare complication resulting from punctured left subclavian vein following insertion of PICC line for total parenteral nutrition. Issue 7 (30th July 2021) - Siddiqui, Saquib Navid; Memon, Muhammad; Hasan, Tanveer
Abstract : This is a rare case of development of bi-lateral chylous pleural effusion (containing parenteral nutrition material) along with pneumomediastinum due to punctured left subclavian vein following insertion of a peripherally inserted central venous catheter (PICC) line. Parenteral nutrition is usually preferred for patients unable to tolerate enteral feeding. Due to hypertonicity of the total parenteral nutrition material, it is usually administered via internal jugular or subclavian vein which have a rapid blood flow; therefore, resulting in adequate mixing. Literature studies are yet to clearly explain the communications between two pleural cavities; therefore, development of bilateral pleural effusions in association with pneumomediastinum makes this case more intriguing. We present the journey of a 43-year-old woman who required insertion of bilateral chest drains, followed by sternotomy and repair of the left subclavian vein after she was found in hypoxic respiratory failure 2 days following insertion of PICC line into her left subclavian vein.